Cell entry of dengue virus - Acosta, Eliana Gisela (2008)
Dengue virus is an expanding public health problem in tropical and subtropical regions of the world, mainly owing to failure in the maintenance of control programs for the mosquito vector Aedes aegypti and increasing and unplanned urbanization. It has been estimated that over 50 million dengue virus infections of varying severity occur globally each year. making this virus the most significant mosquito-borne human pathogen. However, there is no specific antiviral therapy or vaccine for treatment or prevention. This review focuses on recent data describing the putative molecules and mechanisms involved in the complex process of dengue virus binding and entry into mosquito and mammalian cells in primary infections. Furthermore, the perspectives of these early events in the virus life cycle as a target for antidengue therapeutic strategies are also considered.